(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Basic types of derivation of compound adjectives in Old Slavonic language depending on their formal structure and the components belonging to different parts of speech are described. Each of them is shown to found its continuation in modern Slavonic languages having been enriched with new features depending on the peculiarities of each specific language.